Beyond Piety and Politics : Religion, Social Relations, and Public Preferences in the Middle East and North Africa - Çiftçi, Sabri; Shamaileh, Ammar; Wuthrich, F. Michael (Book collections on Project MUSE., 2022)
"How do ordinary men and women in Muslim-majority societies create religion-informed views of political topics such as democracy and economics? Beyond Piety and Politics provides a groundbreaking approach to understanding the depth and variety of political attitudes held by people who consider themselves to be pious Muslims. Using survey data on religious preferences and behavior, the authors argue for the relevance and importance of four outlook categories-Religious Individualist, Social Communitarian, Post-Islamist, and Religious Communitarian-and use these to explore complex and nuanced attitudes of devout Muslims toward issues like democracy and economic distribution. They also reveal how intra-faith variation in political attitudes is not simply doctrinal differences, but also a product of the social aspects of religious association operating within political contexts. By highlighting the dynamic societal and political implications of religious devotion, Beyond Piety and Politics offers a fascinating new theoretical perspective on Islam and politics"--